2004
DOI: 10.1158/0008-5472.can-04-1958
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Listeria Vaccines Containing PEST Sequences Are Potent Immune Adjuvants for the Tumor-Associated Antigen Human Papillomavirus-16 E7

Abstract: Previous work in our laboratory has established that the fusion of tumor-associated antigens to a truncated form of the Listeria monocytogenes virulence factor listeriolysin O (LLO) enhances the immunogenicity and antitumor efficacy of the tumor antigen when delivered by Listeria or by vaccinia. LLO contains a PEST sequence at the NH 2 terminus. These sequences, which are found in eukaryotic proteins with a short cellular half-life, target proteins for degradation in the ubiquitin-proteosome pathway. To invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 22 publications
1
72
1
Order By: Relevance
“…However, subsequent to these earlier experiments, we found that fusion of target Ags to either LLO or a PEST-like sequence contained in LLO resulted in an increased antitumor response (31). The exact reason for this enhancement in immunogenicity of fused Ags is not yet clear, but we hypothesize that these fused Ags are more readily degraded by the proteasome and subsequently targeted to the class I pathway.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, subsequent to these earlier experiments, we found that fusion of target Ags to either LLO or a PEST-like sequence contained in LLO resulted in an increased antitumor response (31). The exact reason for this enhancement in immunogenicity of fused Ags is not yet clear, but we hypothesize that these fused Ags are more readily degraded by the proteasome and subsequently targeted to the class I pathway.…”
Section: Discussionmentioning
confidence: 65%
“…However, we believe that LLO is doing more to increase the immunogenicity of target Ags than simply increasing the degradation and subsequent presentation of these Ags. We compared vaccines where the tumor Ag is fused to LLO vs fusion to PEST and showed that both elicited similar antitumor immune responses (31). However, even fusing the Ag to a LLO molecule from which the PEST sequence has been deleted resulted in better antitumor efficacy than using the Ag alone, suggesting that LLO may have an adjuvant effect quite apart from enhancing Ag processing.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination with LM-LLO-E7 strongly eradicated E7-expressing tumors, while LM-E7 or LM-LLO-E7 (lacking PEST) did not, despite the presence of strong immune responses to E7 in all three vaccine studies. 48,49 Our vaccine studies showed that immunization with LM-LLO was as effective as LM-LLO-Mage-b against 4T1 metastases, despite the presence of strong Mage-b responses in the LM-LLO-Mage-b vaccinated mice. 70 Also, while LM-LLO was highly effective against 4T1 metastases in vivo, LM-OVA was not (unpublished results).…”
Section: Ros-mediated Tumor Cell Kill By Listeriamentioning
confidence: 92%
“…48 Interestingly, vaccination with LM-E7 or LM-LLO-E7 missing the PEST (a sequence rich in proline, glutamic acid, serine and threonine) in the amino terminus of LLO, only induced slower growth of TC-1 tumors, despite strong immune responses to E7. 48,49 The Lm-LLO-E7 vaccine was also tested for its ability to break tolerance to a self-tumor antigen using a mouse that was transgenic for HPV-16, E6 and E7. 50 These mice develop autochthonous thyroid tumors, as the transgene is under the control of the thyroglobulin promoter.…”
Section: Preclinical Studies Of Listeria-based Vaccines In Animal Modmentioning
confidence: 99%
See 1 more Smart Citation